The Role of Teachers in Students' Moral Education at Madrasah - Katni Katni; Nawfal Nawfal; Andre Alvian Sribimo; Juventina Adityas Putri; Gesit Restu Pemanggih; Muhammad Zahrudin (CV. Bimbingan Belajar Assyfa, 2025)
The problem of moral degradation of the young generation of Indonesia is very surprising, starting from free association, corruption, drugs. This researcher aims to analyze the role of teachers in fostering students' morals and the impact of the role of teachers in fostering students' morals and the supporting and inhibiting factors. This study uses a qualitative approach, field research type. Data collection through in-depth interviews, key informants, teachers and students, observation, and relevant documentation. The location of the study at MA Ma'arif Hasan Munadi Ponorogo. Data analysis through reduction, data display and data verification. The results of this study are the role of teachers in student moral education as role models, educators, and facilitators. The impact of these roles produces 6 commendable student morals. While the supporting and inhibiting factors in every educational process are always there, it is only how teachers manage to strengthen the supporting factors and minimize the inhibiting factors. Suggestions if the four roles of teachers are carried out optimally, then the formation of student morals will run effectively and efficiently, and vice versa.